Concept of Ukrainian National Education and Upbringing in Pedagogical Heritage of Ivan Yushchyshyn - Mykhailyshyn, Romana (Pedagogical Discourse, 2015)
In the article the investigations and publications on the topic are used; accent is put on the contribution of profound pedagogues and public people in the development of Ukrainian national school in the second half of the 19th – the beginning of the 20th century. Profound researches of scientists of the end of 20th century – beginning of the 21st century have been mentioned, which revealed the evolution of the idea of national education and national upbringing on the basis of deep historical and pedagogical analyses. Active position of the famous Galician pedagogue Ivan Yushchyshyn on the topic is revealed. On the basis of his pedagogical heritage the main ideas concerning organization of national school and significance of national upbringing for the realization of Ukrainian national idea are analyzed; main aspects of the development of Ukrainian national school and upbringing in Galicia are shown; the most relevant I.Yushhyshyn’s ideas concerning prospects of development and conditions of functioning of Ukrainian national school are emphasized; the relevance of the pedagogue’s pedagogical ideas concerning the concept of national education and upbringing in modern circumstances are traced.